Narrative review of methodological advances in human milk fortification: for better preterm infant growth - Yang, Jiabin; Tang, Qin; Zhou, Ping (Frontiers in Pediatrics, 2024)
It is generally suggested that human milk alone might not be enough to meet the nutritional requirements of very preterm infants, necessitating the use of nutritional fortification. The composition of human milk varies among individuals and changes over time, challenging the assumption that protein content and energy density remain constant during standard fortification. Consequently, it has led to suboptimal body growth rates in most very preterm infants compared to fetuses of the same gestational age. In light of this, personalized fortification and innovative fortification strategies have been introduced. This paper aims to review the importance of fortification and the shortcomings of standard fortification, as well as describe and evaluate the advantages and limitations of various individualized fortifications. The optimal use of human milk fortification, in accordance with the nutrient content of human milk and the physiological maturity and growth of preterm infants, is a crucial aspect of the field of preterm infant nutrition.